(untitled) (Research, Society and Development, 2025)
Chemistry is the science that studies matter, its properties and transformations, encompassing the behavior of elements and the substances they form. Therefore, a deep understanding of the atom, its composition and structure, is essential to understanding chemical phenomena, as it is the fundamental unit of all matter. However, due to the abstract nature and complexity of atomic description, teaching this subject poses significant challenges, especially at the primary and secondary school levels. Therefore, studies that improve the learning of atomic concepts are of great interest. In this study, the objective was to propose a didactic sequence structured in four moments (Initial problematization, Organization of knowledge, Application of knowledge and Systematization and evaluation of content), using the flame test as an experimental resource to illustrate the validity of atomic models and highlight the electronic distribution in atoms. Flame tests were performed with NaCl, KCl, MgSO₄, CaCl₂ and CuSO₄. The results demonstrated the effectiveness of the proposed approach, as evidenced by the students’ high level of engagement, active participation in the experiments and discussion of the results, and their accurate description and interpretation of the applicability of atomic models to the phenomenon under investigation.